Accuracy assessment of urban growth pattern classification methods using confusion matrix and ROC analysis - Ghani N.L.A.; Abidin S.Z.Z.; Khalid N.E.A. (Springer Verlag, 2023)
Classification (of information); Growth rate; Image resolution; Matrix algebra; Pattern recognition; Soft computing; Accuracy assessment; Accuracy of classifications; Classification methods; Confusion matrices; Expansion index; Receiver operating characteristic analysis; ROC analysis; Urban growth patterns; Urban growth